2012
DOI: 10.1177/1099636211433106
|View full text |Cite
|
Sign up to set email alerts
|

Development of damage in some polymeric foam-core sandwich beams under bending loading

Abstract: The damage mechanisms in sandwich plates with polymer foam cores are investigated. There has been a long-standing controversy on what is the weakest element of sandwich plates, the skin-core bonding or the foam core. Under four-point bending of a sandwich plate, we found that in all cases cracks are nucleated inside the polymer foam core as monitored by a high-speed camera. Several separated small cracks develop in the core; then the small cracks are connected and form the main crack that propagates through th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 11 publications
1
5
0
Order By: Relevance
“…In contrast, recently Ayorinde et al. [16] using acoustic emission (AE) and high-speed cameras claimed that the damage in their sandwich systems always started in the core, independant of the face sheets. Similar to Gibson, Ayorinde et al.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, recently Ayorinde et al. [16] using acoustic emission (AE) and high-speed cameras claimed that the damage in their sandwich systems always started in the core, independant of the face sheets. Similar to Gibson, Ayorinde et al.…”
Section: Resultsmentioning
confidence: 98%
“…by Juntikka and Hallstrom [5] and Ayorinde et al. [16], this technique could be also interesting for online investigations of the shear strain in the core material, which is challenging to measure directly and accurately with conventional strain gauges. As mentioned in the experimental section, we only present a short part on the DIC measurements and a comprehensive analysis and discussion will be presented in a future manuscript.…”
Section: Resultsmentioning
confidence: 99%
“…It is believed that the damage in the impacted part may evolve in a different way from that occurring in the tests adopted to determine the damage curve for the model, which is measured under tensile loading. The damage mechanism in sandwich plates with polymer foam cores has been investigated in the literature [ 29 , 30 ], showing the importance of shear stresses developing in the core under bending loads. Similarly, it is recognized that stress triaxiality is relevant in the void growth in damaged materials during the “void coalescence phase”, which anticipates material failure [ 31 ].…”
Section: Discussionmentioning
confidence: 99%
“…The cracks propagate so fast that it is hard to detect the place where the crack was nucleated, in the core or in the skin-bonding area. The damage mechanisms in sandwich plates with polymer foam cores were investigated by Ayorinde et al (2012) using four-point bending tests of a sandwich plate monitored by a high-speed camera. It was found that in all cases, cracks are nucleated inside the polymer foam core.…”
Section: Damage Of Composite Structuresmentioning
confidence: 99%